A Study of Mesh Density on the Surface of a Far Field Sphere: Investigating Mesh Density for Ocean Modeling Applications (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A system for machine mesh generation is proposed for ocean modeling applications. The technique uses a typical methodology to engineer to explain the structure of the mapping domain. Using stereographic coordinates, the underlying sphere is parameterized. Coasts are then represented in stereographic parametric space with cubic splines. In the parametric plane with usable techniques, the mesh creation algorithm constructs the network. This approach allows coastlines to be imported from multiple databases and thus domains with highly variable duration scales to be created. The findings include meshes and computational models of different kinds.